EAST ASIA - REGIONAL OR GLOBAL FINANCIAL INTEGRATION? - S. V. Nozdrev (Vestnik MGIMO-Universiteta, 2018)
The article considers the main directions of further financial integration of East Asian countries, developing deep and stable connections within the framework of global and regional economy. Currently, among the investment flows that lay ground for financial integration with other regions, the leading place is taken by funds from and to the countries of North America and Western Europe. At the same time, the growth in intraregional investment, especially in terms of assets, significantly exceeds growth from the group of developed countries, the share of participation of the latter in interregional relations is gradually decreasing. Through the development of regional integration at various levels of economic interaction, Asian countries are seeking ways to reduce vulnerability and "contagion" from the processes of financial globalization. While the trends in regional financial integration have certain advantages, they also involve some risks. On the one hand, the Asian region can benefit from greater financial diversification and reduce the concentration and dependence from western economies. On the other hand, this process can bring imported volatility from other countries of the region and reduce the regulatory counteraction from various types of shocks that arise in the economies of these countries and beyond. The intensity of further convergence of the financial markets and institutional arrangements of Asian countries will be largely determined by the scenarios of development of the world economy, as its slowdown and, consequently, decrease of activity in the global capital market clearly leads to strengthening of regional integration processes. The expansion of intraregional cross-border financial transactions requires a significant expansion of the regulatory framework for cooperation, the conclusion of two-and multilateral banking and investment agreements, as they directly determine the process of capital flows liberalization. As regional financial cooperation in Asia has not yet developed as in Western Europe and North America, it is important to pay attention to such essential elements as economic and financial supervision, normative harmonization of banking and securities market, strengthening of regional financial security system and maintenance of development of various segment of financial market, first of all bonds in local currency. In the process of work the basic methods of economic analysis were applied, namely basic system and statistical methods. The use of the system approach allowed to consider the movement of capital flows from an to Asia over a long period of time, the evolution of financial integration models. Calculations and comparisons, the construction of tables was carried out on the basis of statistical methods, which are applied for the study of currency and credit relations. The information base of the studies was based on reports and statistics of the World Bank (IBRD), the International Monetary Fund (IMF), the Asian Development Bank, as well as analytical materials of the Institute of World Economy and International Relations of RAS.